LPV model based gain-scheduling controller for a full vehicle active suspension system - Onat, Cem; Kucukdemiral, Ibrahim B.; Sivrioglu, Selim; Yuksek, Ismail (SAGE PUBLICATIONS LTD, 2007)
This article addresses the design of a gain-scheduling type nonlinear controller for a full-vehicle active suspension system. The proposed method is based on a Linear Parameter Varying (LPV) model of the system. In this model, the variations in suspension deflection and mass are chosen as the scheduling parameters. During the simulations, the full-vehicle system that is controlled by the proposed method is tested with different road profiles, having high and low bumps, hollows and combinations of the two. The simulation results demonstrate that the proposed method successfully maximizes the ride comfort when suspension deflection is far away from the structural limits and minimizes the suspension deflection by changing its behavior when the suspension limits are reached.
Keywords: LPV systems; active suspension control; gain-scheduling control; CAR MODEL; DESIGN; Acoustics; Engineering; Mechanics